To solve the system of equations, we can use the method of substitution or elimination.
Let's solve it using the method of substitution:
From the second equation, we can isolate x:
x - 5y = -20
x = 5y - 20
Now substitute this expression for x in the first equation:
-4(5y - 20) + 6y = 38
-20y + 80 + 6y = 38
-14y + 80 = 38
-14y = -42
y = 3
Now substitute y = 3 into the second equation to find x:
x - 5(3) = -20
x - 15 = -20
x = -20 + 15
x = -5
Therefore, the solution to the system of equations is (x, y) = (-5, 3).
So the correct response is: (-5, 3)
Solve the system of equations.%0D%0A−4x+6y=38 %0D%0Ax−5y=−20 (1 point)%0D%0AResponses%0D%0A%0D%0A(5, 3)%0D%0Aleft parenthesis 5 comma 3 right parenthesis%0D%0A%0D%0A(−35, −3)%0D%0Aleft parenthesis negative 35 comma negative 3 right parenthesis%0D%0A%0D%0A(−5, 3)%0D%0Aleft parenthesis negative 5 comma 3 right parenthesis%0D%0A%0D%0A(35, −3)
1 answer